What was authoritative for Chronicles? - Ben Zvi, Ehud; Edelman, Diana Vikander (Eisenbrauns, 2011)
One size does not fit all : observations on the different ways that Chronicles dealt with the authoritative literature of its time / Ehud Ben Zvi -- Judging a book by its citations : sources and authority in Chronicles / Steven J. Schweitzer -- Chronicles as consensus literature / David A. Glatt-Gilad -- Chronicles and the definition of "Israel" / Philip R. Davies -- Ideology and utopia in 1-2 Chronicles / Joseph Blenkinsopp -- Cracks in the male mirror : references to women as challenges to patrilinear authority in the genealogies of Judah / Ingeborg Löwisch -- Araunah's threshing floor : a lesson in shaping historical memory / Yairah Amit -- The Chronicler and the Prophets ; who were his authoritative sources? / Louis Jonker -- The Chronicler's use of the Prophets / Amber K. Warhurst -- Rethinking the "Jeremiah" doublet in Ezra-Nehemiah and Chronicles / Mark Leuchter -- Sociology and the book of Chronicles : risk, ontological security, moral panics, and types of narratives / David J. Chalcraft -- Chronicles and local Greek histories / Diana Edelman, Lynette Mitchell